STUDY ON BROADCAST MESSAGE PERFORMANCE ON VEHICULAR AD HOC NETWORK - EBN-AZAR DIGEPUAFELA GAD POLLO (NIM: 23206007), DON
One of Vehicular Ad hoc Network (VANET) application is for safety application. In this applications, informations which are exchanged among vehicles are called safety message. Broadcast method is the dominant way in distributing safety message in VANET. Safety message includes periodic message to inform vehicle status and event message to inform an event. In DSRC standard, periodic message should be transmitted every 100 ms. Packet size in SAE standard is 100 – 500 byte. To keep the information up to date, time duration should be less than 100 ms. The information distribution must cover all vehicles within range of the transmission. This research analyzes the effect of transmission rate, packet size and transmission power on VANET parameter which are reception rate and access delay time for the variation of vehicle density. From the result of this research, for status up-date every 100 ms, maximum reception rate 87.14 %, obtained from transmission rate of 10 packet/second, packet size 100 byte, transmission power 0.28 mW and 50 nodes. Whereas, for time duration less than 100 ms, maximum value of access delay time 15 ms obtained from transmission rate of 10 packet/second, packet size 100 byte, transmission power 0.78 mW and 400 nodes. From that result, transmission rate of 10 packet/second and packet size of 100 byte are chosen.